An Experimental performance of Eliane Radigue's early feedback works - Parra Cancino, Juan; Vintage Materialities in Music Orpheus Institute, Ghent June 28-30, 2023 (Ghent Orpheus Institute, 2023)
Lecture and performance.
Vintage Materialities, an intercluster, interinstitutional collaboration.
FRIS
1
Keywords: Music, Thought and Technology